EFEKTIVITAS KEBIJAKAN DAN KESIAPAN KELEMBAGAAN UKM INDONESIA DI ERA TRANSISI HIJAU: ANALISIS BERDASARKAN INDEKS KEBIJAKAN UKM ASEAN 2024 - Yunita Yusuf, Yulia; Rais, Anisatun Humayrah; Anas, Agung Muliaman; Gaffar, Andi Nurrahma; Faisal, Andi (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the effectiveness of Indonesia’s government policies and institutional readiness in supporting the green transition of the MSME sector based on the ASEAN SME Policy Index 2024. The research employs a descriptive–comparative approach and exploratory qualitative analysis through a review of index documents, national policy reports, and international publications. The results show that Indonesia has experienced an increase in scores across almost all SMEPI dimensions since 2018, especially in access to finance and digitalization of SMEs. However, Indonesia’s achievements remain low in the dimensions of Greening SMEs and Social & Inclusive Enterprises, indicating that the integration of environmental and social aspects into MSME policies has not yet become a primary priority. In terms of policy effectiveness, three national programs—SEHATI (BPJPH), the Green Financing Roadmap (OJK), and the Green Industry Program (Ministry of Industry)—have high relevance to the green transition, but their implementation effectiveness remains limited due to policy fragmentation and low green literacy among MSME actors. Institutional analysis indicates that Indonesia continues to face constraints in technical capacity, inter-ministerial coordination, and governance, particularly the lack of data-driven monitoring mechanisms and an integrated performance evaluation system for green policies. Overall, the study finds an institutional gap between policy design and implementation. These findings highlight the need for cross-sector policy harmonization, strengthening of green regulations and financing, and the development of data-based monitoring systems to support the transformation of MSMEs toward a green economy.